Dottie - Gurnah, Abdulrazak (London Bloomsbury Publishing, 2021)
Dottie Badoura Fatma Balfour finds solace amidst the squalor of her childhood by spinning warm tales of affection about her beautiful names. But she knows nothing of their origins, and little of her family history - or the abuse her ancestors suffered as they made their home in Britain.
Keywords: Fiction